Ferroelectric field-effect transistors based on HfO2: a review. (22nd September 2021) - Mulaosmanovic, Halid; Breyer, Evelyn T; Dünkel, Stefan; Beyer, Sven; Mikolajick, Thomas; Slesazeck, Stefan
Abstract: In this article, we review the recent progress of ferroelectric field-effect transistors (FeFETs) based on ferroelectric hafnium oxide (HfO2 ), ten years after the first report on such a device. With a focus on the use of FeFET for nonvolatile memory application, we discuss its basic operation principles, switching mechanisms, device types, material properties and array structures. Key device performance metrics such as cycling endurance, retention, memory window, multi-level operation and scaling capability are analyzed. We also briefly survey recent developments in alternative applications for FeFETs including neuromorphic and in-memory computing as well as radiofrequency devices.